2010
DOI: 10.1186/ar3121
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between patient-reported disease severity in osteoarthritis and self-reported pain, function and work productivity

Abstract: IntroductionUnderstanding the relationship between patient-reported osteoarthritis (OA) severity and other patient-reported outcomes in the real-world clinical setting can provide a basis for appropriate patient management. The objective of this study was to determine how patient-reported OA severity correlates with patient-reported outcomes including pain, function and productivity.MethodsWe used the Adelphi Disease Specific Programme (DSP) for OA, a database aggregated from large, multinational, observationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
58
0
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 27 publications
10
58
0
5
Order By: Relevance
“…29,30 In our study, the prevalence of OA was higher in subjects with hypertension, cardiovascular disorders and diabetes. These comorbidities have also been reported by other authors, along with depression, dyslipidemia or other musculoskeletal conditions.…”
Section: Discussionsupporting
confidence: 43%
“…29,30 In our study, the prevalence of OA was higher in subjects with hypertension, cardiovascular disorders and diabetes. These comorbidities have also been reported by other authors, along with depression, dyslipidemia or other musculoskeletal conditions.…”
Section: Discussionsupporting
confidence: 43%
“…29,30 No nosso estudo, a prevalência de OA foi maior em indivíduos hipertensos, com transtornos cardiovasculares e diabetes. Essas comorbidades também foram relatadas por outros autores, juntamente com depressão, dislipidemia ou outros problemas musculosqueléticos.…”
Section: Discussionunclassified
“…4,13,30 Em nosso estudo, também observamos uma associação entre dor medida por EVA e impacto na vida diária, gravidade da doença e nível de incapacitação. Segundo a literatura, o alí-vio da dor é o principal motivador nos pacientes com OA, na busca de atenção médica.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…A patient's tendency to feel joint pain with increasing Osteoarthritis (OA) severity [1] has been reported and hip-joint pain is a factor that reduces Short Form 36 physical functioning [2] and walking speed [3]. Moreover, Mannoni et al [4] have reported that hip OA is strongly associated with disability, and Hall et al [5] have reported that hip OA causes decreased physical functioning on the Western Ontario and McMaster Universities Osteoarthritis Index.…”
Section: Introductionmentioning
confidence: 99%